Evaluation of Seismic Behaviour in Defensive Tunnels with Oval and Rectangular Cross-Sections in Loose and Dense Soils - Peyman Farhadi Yeganeh (Journal of Global Pharma Technology, 2017)
Underground spaces are frequently applied in defense areas due to their natural and environmental conditions. Passive defense is a good tool for reducing the possible losses and increasing the efficiency of these structures. By studying the past events, it can be observed that, despite the popular belief, these structures have incurred irreparable damages during the earthquake. To this end, the present paper evaluated the seismic behavior of two specimens of rectangular and oval tunnels applied in passive defense using the plaxis 2D software. These structures were placed under three particular earthquake accelerographs in a dense and loose soil (soil environment of Bandar Abbas), and it was attempted to study the seismic behavior of these tunnels affected by the form of the structure and the soil-structure interaction using this dynamic analysis. The analysis of results showed that the earthquake had a greater impact on rectangular tunnels in loose soil, and the construction of oval tunnels will be more justified in the environment of Bandar Abbas.Keywords: Underground spaces, Passive defense, Earthquake, Soil-structure interaction.